2010
DOI: 10.1093/jac/dkq396
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli carrying extended-spectrum  -lactamases (CTX-M and TEM-52) from broiler chickens and turkeys in Great Britain between 2006 and 2009

Abstract: poultry-derived CTX-M E. coli in GB are different from major CTX-M sequence types causing disease in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
131
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 31 publications
22
131
3
1
Order By: Relevance
“…Similar results have been reported by Randall et al [13] , Overdevest et al [3] , Morris et al [26] , and Leverstein-van Hall et al [27] . Also, the majority of those ESBL genes were identified as bla CTX-M-1 (81.8%) in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results have been reported by Randall et al [13] , Overdevest et al [3] , Morris et al [26] , and Leverstein-van Hall et al [27] . Also, the majority of those ESBL genes were identified as bla CTX-M-1 (81.8%) in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of ESBL producing E. coli has been reported between 6.7% and 60.7%. Our results were relatively low according to some studies [9,13] while showed similarities to others [11,12] .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A major concern is the high prevalence of these resistant bacteria in the broiler production chain. ESBL‐/pAmpC‐producing Enterobacteriaceae were frequently isolated from broiler fattening farms worldwide (Bortolaia et al ., 2010; Randall et al ., 2011; Kameyama et al ., 2013; Maciuca et al ., 2015; Trongjit et al ., 2016) but were also found in broiler (grand) parent flocks (Dierikx et al ., 2013; Agersø et al ., 2014; Mo et al ., 2014; Zurfluh et al ., 2014). Therefore, different transmission scenarios of the resistant bacteria in the broiler production pyramid are discussed: A transmission from prior stages into the fattening farms (Giovanardi et al ., 2005; Dierikx et al ., 2013; Nilsson et al ., 2014; Huijbers et al ., 2016) as well as an insufficient cleaning and disinfection procedure in the chicken barns (Hiroi et al ., 2012; Luyckx et al ., 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The gastro-intestinal tract of animals is a reservoir for bacteria carrying β-lactamases and a potential source of human pathogens. In particular, ESBL has been described in healthy poultry, in faecal samples of broilers and also in broiler chicken caecal samples and turkey flocks (Costa et al 2009;Bortoloaia et al 2011;Randall et al 2011). Recently, a high prevalence (100%) was found in faecal samples of broilers in Germany, while no ESBLs producing bacteria were observed in turkey farms (Friese et al 2013).…”
mentioning
confidence: 99%